Inference Generation During Text Comprehension by Adults With Right Hemisphere Brain Damage: Activation Failure Versus Multiple Activation. - Tompkins, Connie A.; Fassbinder, Wiltrud; Blake, Margaret Lehman (Journal of Speech, Language & Hearing Research, 2004)
Evidence conflicts as to whether adults with right hemisphere brain damage (RHD) generate inferences during text comprehension. M. Beeman (1993) reported that adults with RHD fail to activate the lexical-semantic bases of routine bridging inferences, which are necessary for comprehension. But other evidence indicates that adults with RHD activate multiple interpretations in various comprehension domains. In addition, the activation of contextually inappropriate interpretations is prolonged for many adults with RHD and predicts poor discourse comprehension. This study contrasted Beeman's activation failure hypothesis with the prediction that adults with RHD would generate multiple interpretations in text comprehension. The relation between activation of textually incompatible inferences and discourse comprehension was also investigated for this group. Thirty-seven adults with RHD and 34 without brain damage listened to brief narratives that required a bridging inference (BI) to integrate the text-final sentence. This final sentence, when isolated from its text, was strongly biased toward a contextually incompatible alternate interpretation (AI). Auditory phoneme strings were presented for lexical decision immediately after each texts initial and final sentence. Adults with RHD were both faster and more accurate in making lexical decisions to BI-related target words in final-sentence position than in initial-sentence position. Thus, contrary to the activation failure hypothesis, adults with RHD generated the lexical-semantic foundations of BIs where they were required by the text. Al generation was evident in accuracy data as well, but not in response time data. This result is partially consistent with the multiple activation view. Finally, greater activation for contextually incompatible interpretations was associated with poorer discourse comprehension performance by adults with RHD. Reprinted by permission of the publisher.